Peran Guru Dalam Meningkatkan Motivasi Belajar Dan Prestasi Peserta Didik Sekolah Dasar - Nabila Mutia Sukma; Regita Indah Pertiwi; Dewi Anggi Agustin; Ujang Jamaludin; Sigit Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the important roles played by the teacher is to increasestudent learning motivation, besides being tasked with impartingknowledge the teacher must also increase student learningmotivation and achievement. Giving motivation is done so thatstudents have a passion for learning and become high achievingstudents. This study aims to determine the teacher's role inincreasing learning motivation and student achievement. Themethod used in this research is a descriptive qualitative methodwith the type of literature study research. The results of the studyshow that the teacher has a very important role in the learningprocess, the role of the teacher can encourage student learningmotivation and motivate students to achieve their learningachievements.